Electrifying the production of sustainable aviation fuel: the risks, economics, and environmental benefits of emerging pathways including CO2. Issue 11 (14th October 2022) - Grim, R. Gary; Ravikumar, Dwarak; Tan, Eric C. D.; Huang, Zhe; Ferrell, Jack R.; Resch, Michael; Li, Zhenglong; Mevawala, Chirag; Phillips, Steven D.; Snowden-Swan, Lesley; Tao, Ling; Schaidle, Joshua A.
Abstract : Emerging CO2 to SAF pathways facilitates diversification of fuel production with the potential for a near carbon neutral footprint. Abstract : Due to challenges related to weight and travel distance, the medium to long-haul aviation sector is expected to remain reliant on liquid hydrocarbon fuels into the foreseeable future, representing a persistent source of CO2 emissions within the anthropogenic carbon cycle. As the world grapples with the environmental fallout from rising CO2 emissions, a prevailing strategy to mitigate the impact of air travel is through the utilization of sustainable aviation fuels (SAF) produced from biogenic carbon sources such as fats, oils, greases, and biomass. However, with the demand for SAF expected to grow substantially in the coming decades, there is concern around the availability of these feedstocks at scale. Recent studies have proposed that this potential gap in supply could be closed by utilizing CO2 as a complementary source of carbon combined with renewable electricity to drive the chemical transformation. In this study, a cross-cutting comparison of an emerging CO2 -to-SAF pathway with existing routes to SAF is performed, revealing the potential for CO2 -derived SAF to be competitive both in terms of costs and carbon intensity, further diversifying future options for SAF and providing a complementary option for the conversion of CO2 -to-SAF beyond the decades old methanol to olefins (MTO) and Fischer–Tropsch (FT) technologies. In addition, we discuss potential technical, market, and systems integration risks for the ultimate scale-up and commercialization of the pathway identified herein.